LiteratuRA, com R - de RONDÔNIA e A - de MULHER: a leitura na escola - Silva, Elisangela Onezorg da (2023)
This study, entitled Literature with R, by RONDÔNIA and A, by WOMAN: reading at school is part of the line of research Reading and Reader Training, and presents, as its theme, the reading at school of female authorship literature produced in the state of Rondônia aiming at literary literacy. The objective is to develop reading practices in the classroom, from the perspective of literary literacy, with literature written by women from Rondônia, evaluating the students' reading experiences. he choice for this approach stemmed from the need to review the teaching of literature based on literary schools that favor one group while marginalizing others. For this, Candido (2006) and Petit (2009, 2013) will be mobilized as a theoretical foundation regarding literary reading; in turn, Cosson (2021a), Kleiman (2016), Colomer (2007) and Reyes (2012) will cover the role of the school and the teacher as reading mediators; in relation to the readers' profile, the base will be provided by Santaella (2007, 2013), Tavares (2019) and research data carried out by the Instituto Pró-livro (2019). Furthermore, the studies of Cosson (2021b, 2021c), Paulino (2010) and Soares (2010) will offer a base to deal with literary literacy. In addition, the Traditional Model of literary teaching will be discussed under the eyes of Fischer (2021), and a brief retrospective will be made on the insertion of women in Brazilian literature based on Freitas (2021), Duarte (2003), Muzart (2003), Grecco (2018) and Da Fonseca (2022). Identity and diversity, with concepts from Woodward and Hall (2014), will also be discussed. This work was developed, regarding its nature, as an applied research; in relation to the objectives, it is an exploratory research; with regard to the approach of its problem, it is a qualitative study; regarding technical procedures, it is a bibliographical, documental and action research with 23 students from a first-year high school class at Escola Dayse Mara de Oliveira Martins, located in Jaru, state of Rondônia, through a basic sequence of texts from the book Childbirth (di) verses (2022), published by the Rondônia Writers Club. The results show that working with publications by female authors from the state of Rondônia arouses the interest of students because they are authors from the same time and region, in addition to the themes addressed in the texts which communicate with these readers in formation